Czy można odkryć istnienie zależności przyczynowo-skutkowych w obrębie zjawisk badanych przez psychologię? Kategoria przyczynowości i badania eksperymentalne w psychologii - Bobryk, Jerzy (Filozofia Nauki, 1994)
The author attempts to show that, despite the recent development of the methodology of scientific researches in psychology, the experimental approach does not enable us to discover the factual causal links among psychological phenomena. The real function of the category of causality is described and discussed.